More adult-born dentate gyrus neurons to weaken cocaine-related retrograde memories: an in vivo strategy employing exogenous lysophosphatidic acid - Ladrón de Guevara-Miranda, David; Moreno-Fernández, Román D.; Gil Rodríguez, Sara; Rosell-del-Valle, Cristina; Estivill-Torrús, Guillermo; Serrano, Antonia; Pavón-Morón, Francisco Javier; Rodriguez-de-Fonseca, Fernando; Santín-Núñez, Luis Javier; Castilla-Ortega, María Estela (My University, 2019)
The post-training enhancement of adult hippocampal neurogenesis (AHN) has been receiving growing interest as a potential method to manipulate retrograde memories. Recent hypothesis suggest that the addition of adult-born dentate granule cells might promotes remodeling of pre-existing hippocampal circuits, which might both clear cocaine-related memories and facilitate the learning of new adaptive information. Here, we study the effect of stimulating AHN in vivo with exogenous lysophosphatidic acid (LPA) on the maintenance of retrograde cocaine-contextual associative memories. Male C57BL/6J mice trained in a cocaine-induced Conditioned Place Preference (CPP) model were later submitted to repeated intracerebroventricular (i.c.v.) injections of LPA, Ki16425 or vehicle solution during withdrawal. Afterwards, the long-term persistence of the cocaine-CPP was assessed and the mediational role of AHN in this process was evaluated. In addition, wild-type and mice lacking the LPA1 receptor received a single i.c.v. injection of LPA, Ki16425 or vehicle to assess the role of the LPA1 receptor in the LPA-induced increase of AHN. Our results revealed that the chronic administration of LPA decreased the retention of a previously acquired cocaine-induced CPP. This effect was mediated by an LPA-induced increase of AHN. In contrast, mice treated with Ki16425 showed reduced cocaine-CPP retention, but they increased their preference for the cocaine-paired compartment throughout CPP extinction. Besides, no effects of Ki16425 on AHN were found. Immunohistochemical studies suggested that LPA stimulated cell proliferation and promoted neuronal maturation with a key role of the LPA1 receptor. These findings emphasize the relevance of LPA and its LPA1 receptor as an in vivo modulator of AHN and the utility of the post-training increase of adult-born hippocampal neurons to weaken cocaine-context associations.
Keywords: Toxicomanía - Tratamiento; Experimentación animal; Cocaina; Hipocampo (Cerebro); Neurobiología del desarrollo; Cocaine; Adult hippocampal neurogenesis; Lysophosphatidic acid; Conditioned Place Preference; Memory